Regional Economic Outlook, April 2009, Sub-Sarahan Africa. (Regional Economic Outlook, 2009)
Prepared by the IMF African Department, and published twice a year in English and French, Regional Economic Outlook: Sub-Saharan Africa analyzes the macroeconomic performance and short-term prospects of sub-Saharan Africa and provides and in-depth analysis of selected topics. The April 2009 Outlook includes two chapters: one on the macroeconomic impact of the global financial crisis on sub-Saharan Africa, and the other on the impact of the crisis on financial systems in the region. Detailed country data are provided in a statistical appendix.